Electrochemical tailoring of Pb-free Sn coatings modified with SiC nanoparticles by surfactant-assisted reverse pulse plating - Sharma, Ashutosh; Ahn, Byungmin (Applied Surface Science, 2021)
In this study, reverse pulse plating technique was used to study the effect of various surfactants (anionic, non-ionic, and cationic) in electrolytes and incorporation of SiC nanoparticles (NPs) in the Sn matrix. The microstructural and electrochemical observations indicate that the incorporation of SiC in Sn coating depends upon the type of surfactants. The composite stress moves from compressive to tensile with SiC content. The maximum grain refinement of Sn-SiC coatings was found in the presence of a cationic surfactant in the electrolyte while a minimum value of resistivity was displayed by coatings prepared in anionic surfactant. The corrosion behavior of Sn-SiC coatings showed superior corrosion protection ability of non-ionic surfactants amongst other surfactants used here.
Keywords: Corrosion behavior; Micro-structural; Minimum value; Reverse pulse plating; SiC coatings; Sic contents; SiC nanoparticles; Surfactant assisted; Co-deposition; Composite; Corrosion; Pulse reverse; Solder; Surfactant